The Effect of Fenugreek Seed (Trigonella Foenun gracem) and Zinbiber Officinal Rhizome in Rations on Some Production and Physiological Performance in Broiler Chicks - AL-KASSIE, GALIB A.M.; S.A.AL-Nassery, Jinan (The Iraqi Journal of Veterinary Medicine, 2009)
The study was conducted to investigate the effect of Fenugreek and Ginger Powder. The additiveswere added to diets of broiler chicken for 6 weeks (along the period of experiments). The Productionperformance, the Physiology and the Microbial balance in the intestine were studied.150 day-old Hubbard Chicks were divided randomly into 5 groups were as follow:1- Group one: Basal diet (control group).2- Group Two: Basal diet to 0.5 % Fenugreek.3- Group Three: Basal diet to 1 % Fenugreek.4- Group Four: Basal diet to 0.5 % Ginger.5- Group Five: Basal diet to 1 % Ginger.The results showed:1- The groups which treated by Fenugreek seeds powder (0.5 %) and by Ginger (0.5 %)and (1%) showed insignificant increase in body weight compared with T1.2- The groups which treated by Fenugreek seeds powder (1%) showed significantdecrease (P<0.05) in body weight compared with other groups.3- There was no significant differences in the feed conversion coefficient betweendifferent groups.4- Improvement of blood parameters of T2, T3 , T4 and T5 compared with T1.